2014
DOI: 10.1089/gtmb.2013.0386
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-16 Gene Polymorphisms rs4778889, rs4072111, rs11556218, and Cancer Risk in Asian Populations: A Meta-Analysis

Abstract: The rs11556218 T/G polymorphism of the IL-16 gene was significantly associated with elevated cancer risk in Asian populations. Our results warrant larger, better-designed studies, including a greater ethnic variety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In agreement with our results, two other metaanalyses published in 2014 did not find a significant association between rs4778889 and rs4072111 of IL16 and cancer. However, these same studies observed a statistically significant association between rs11556218 and cancer, an association observed in our study with the addition of new studies published after these metaanalyses results [41][42][43][44]. The SNP rs11556218, consisting of a substitution of the T nucleotide by a G, is located in the exon region of the gene and results in a modification of the pro-IL-16 PDZ2 domain (IL-16 isoform with 631 amino acids) and npro-IL-16 (neuronal IL-16 isoform with 1331 amino acids).…”
Section: Discussionsupporting
confidence: 62%
“…In agreement with our results, two other metaanalyses published in 2014 did not find a significant association between rs4778889 and rs4072111 of IL16 and cancer. However, these same studies observed a statistically significant association between rs11556218 and cancer, an association observed in our study with the addition of new studies published after these metaanalyses results [41][42][43][44]. The SNP rs11556218, consisting of a substitution of the T nucleotide by a G, is located in the exon region of the gene and results in a modification of the pro-IL-16 PDZ2 domain (IL-16 isoform with 631 amino acids) and npro-IL-16 (neuronal IL-16 isoform with 1331 amino acids).…”
Section: Discussionsupporting
confidence: 62%
“…The positive association was also observed in nasopharyngeal carcinoma 31 32 , prostate cancer 34 , and glioma 37 . Meta-analysis conducted by two independent groups confirmed these findings of IL16 rs11556218 increasing cancer risk 41 42 . In agreement with these results, we found that the rs11556218 TG/GG genotypes had a 1.66-fold increased risk of developing OS.…”
Section: Discussionmentioning
confidence: 57%
“…Our results were consistent with the negative effect. We failed to find any association between IL16 rs4778889 polymorphism and OS risk, which was verified by three independent meta-analyses 41 42 43 .…”
Section: Discussionmentioning
confidence: 78%
“…This variant was also associated with the risk of osteoporosis in postmenopausal women, although there was no significant alteration in serum cytokine levels [40]. This SNP has also been associated with many types of cancer [41]. In patients with osteosarcoma, IL16 variants were related to higher levels of IL-16 and, consequently, in the effects in the production of other tumor-related inflammatory cytokines, such as TNF-α and IL-1β [42].…”
Section: Plos Onementioning
confidence: 99%